A molecular dynamics simulation on the atomic mass sensor made of monolayer diamond. (31st August 2021) - Zhao, Demin; Wang, Jiangwei; Hao, Peng; Yin, Yaode; Liu, Jianlin
Abstract: The recently synthesized monolayer diamond—diamane has proved to possess excellent mechanical and electrical properties, and it holds great potential in the field of nano-mass sensors. Herein, a molecular dynamics (MD) simulation is employed to systematically investigate the vibration response of the diamane nanoribbon (DNR) for the mass inspection. The results show that under different attached masses, the natural frequency of DNR is about three times of that of the bilayer graphene nanoribbon (BGNR) with the same size. The edge flatness of the DNR can be maintained during the vibration process, while the edge of the BGNR will warp in the initial state. Increasing the pre-strain can significantly increase the natural frequency of the DNR, leading to a higher response sensitivity of the DNR. In addition, the DNR has a higher mass resolution than the BGNR, and can detect smaller attached mass. The position of the attached mass in the resonator has a significant effect on the detection response. When the attached mass is near the center of the resonator, the frequency shift reaches the maximum value, and then it rapidly decreases to zero when the attached mass is close to the edge of DNR. Finally, the attached mass has no obvious effect on the quality factor of the DNR, and its value is stable between 10 5 and 10 6 orders of magnitude. The theoretical results demonstrate the accuracy of the MD results. The MD simulations reveal that the DNR has important implications as a resonant material for nano-mass sensor in the future.